The Law on Granting Joint Assets to Children from Siri Marriage (Analysis of Decision Number 283/Pdt.G/2019/MS. Bna): Hukum Terhadap Hibah Harta Bersama Kepada Anak Hasil Nikah Siri (Analisis Putusan Nomor 283/Pdt. G/2019/MS. Bna) - Amri, Aulil; Iflah, Tajul (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2022)
This article is motivated by the case at the Syar'iyah Court of Banda Aceh in Decision Number 283/Pdt.G/2019/Ms.Bna regarding grants originating from joint assets given to children from unregistered marriages. Even though the property is a joint property between a legal husband and wife obtained during the marriage period with a legal wife, in the property there is still part of the rights of the legal wife or first wife. However, the husband and wife donate the property to the child of the siri marriage without having the permission of the first wife. Therefore, researchers are interested in examining how the fiqh provisions relate to grants of joint property to children resulting from unregistered marriages, why the Panel of Judges of the Banda Aceh Syar'iyah Court rejected the plaintiff's lawsuit against the cancellation of joint property grants to children resulting from unregistered marriages, and what is the basis for the legal considerations. The research methods used are field research and library research. The results of the study state that the provisions in fiqh on the grant of joint property to children resulting from unregistered marriages are valid if there is permission from both parties who own the joint property. If a joint property grant is given to a child resulting from an unregistered marriage without permission from one of the donors, then the grant is invalid, because the condition for the property to be donated must be mil kultam, that is own property may not donate other people's property. The panel of judges at the Banda Aceh Syar'iyah Court rejected the plaintiff's claim against the cancellation of the joint property grant to a child resulting from an unregistered marriage in decision number 283/Pdt.G/2019/Ms.Bna because the case contained a formal defect in which the plaintiff occupied a minor. In Defendant III, minors do not have legal standing as litigants, that is, they do not have legal standing. Therefore, the judge could not accept the case. The plaintiff may re-file a lawsuit for the cancellation of the joint property grant (a new lawsuit) by not placing a minor as defendant III, only then can the judge process the case again.